2020
DOI: 10.1037/bul0000270
|View full text |Cite
|
Sign up to set email alerts
|

Biological aging in childhood and adolescence following experiences of threat and deprivation: A systematic review and meta-analysis.

Abstract: Life history theory argues that exposure to early life adversity (ELA) accelerates development, although existing evidence for this varies. We present a meta-analysis and systematic review testing the hypothesis that ELA involving threat (e.g., violence exposure) will be associated with accelerated biological aging across multiple metrics, whereas exposure to deprivation (e.g., neglect, institutional rearing) and low-socioeconomic status (SES) will not. We meta-analyze 54 studies (n ϭ 116,010) examining associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
203
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 299 publications
(232 citation statements)
references
References 303 publications
(492 reference statements)
26
203
2
1
Order By: Relevance
“…Previous work has documented that amygdala–mPFC functional connectivity may change differentially for those with and without early adversity exposure ( Gee et al, 2013a ; Thijssen et al, 2017 ). Yet, it is worth noting that a recent meta-analysis and review found support for the hypothesis that early adversity accelerates biological aging, but found no consistent evidence for altered amygdala–mPFC connectivity ( Colich et al, 2019 ). Several studies supported potential stress-related acceleration ( Colich et al, 2017 ; Gee et al, 2013a ; Keding and Herringa, 2016 ) and several others that indicated potential delayed development of this circuitry ( Cisler et al, 2013 ; Marusak et al, 2015 ; Silvers et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has documented that amygdala–mPFC functional connectivity may change differentially for those with and without early adversity exposure ( Gee et al, 2013a ; Thijssen et al, 2017 ). Yet, it is worth noting that a recent meta-analysis and review found support for the hypothesis that early adversity accelerates biological aging, but found no consistent evidence for altered amygdala–mPFC connectivity ( Colich et al, 2019 ). Several studies supported potential stress-related acceleration ( Colich et al, 2017 ; Gee et al, 2013a ; Keding and Herringa, 2016 ) and several others that indicated potential delayed development of this circuitry ( Cisler et al, 2013 ; Marusak et al, 2015 ; Silvers et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that stress “accelerates” the development of amygdala–mPFC circuitry is based in part on rodent research ( Callaghan and Richardson, 2011 ; Moriceau and Sullivan, 2006 ). In humans, there is some evidence that amygdala–mPFC connectivity is affected by stress experienced during childhood, yet as noted by a recent review ( Colich et al, 2019 ), approximately half of these studies indicate more positive amygdala–mPFC connectivity, whereas the other half indicate less positive connectivity in those children exposed to early adversity. In adults, alterations of this circuitry is linked to anxiety (e.g., Casey and Lee, 2015 ) and emotion regulation (e.g., Banks et al, 2007 ; Ochsner and Gross, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that the association between ELS and pubertal timing is limited to threatrelated ELS. 41 Therefore, we excluded physical and emotional neglect from the total ELS score. To limit the ELS score to early life and before puberty, we only included items endorsed as having occurred before age 7.…”
Section: Control Variablesmentioning
confidence: 99%
“…There was no consistent association of ELA with amygdala-PFC connectivity. These findings suggest specificity in the types of early environmental experiences associated with accelerated biological aging and highlight the importance of how accelerated aging contributes to health disparities and whether this process can be mitigated through early intervention” ( Colich et al, 2019 , p. 2).…”
Section: Introductionmentioning
confidence: 96%
“…It is interesting that such individualized prevention strategies increasingly receive interdisciplinary support. To mention just one example: A meta-analysis by Colich et al (2019) found that early-life adversity (ELA) involving threat (e.g., violence exposure) was associated with accelerated biological aging across multiple metrics, whereas exposure to deprivation (e.g., neglect, institutional rearing) and low socio-economic status (SES) was not. The authors meta-analyzed 46 studies ( n = 64,925) the examining association of ELA with pubertal timing and cellular aging (telomere length and DNA methylation age) in order to understand the short and long-term consequences of early-life adversities in detail and to take corrective action in an individual way.…”
Section: Introductionmentioning
confidence: 99%